EVOLUTION OF TRANSLATION THEORIES: FROM LITERAL TO COMMUNICATIVE APPROACHES (Ustozlar uchun, 2026)
This article explores the evolution of translation theories, tracing their development from early literal approaches to modern communicative and functionalist paradigms. The study examines how translation practices have shifted from a strict focus on word-for-word equivalence to a more nuanced understanding of meaning, context, and purpose. Key translation models, including literal, free, dynamic equivalence, and skopos-based approaches, are analyzed to highlight their theoretical foundations and practical implications. The article also discusses the influence of cultural, linguistic, and sociopolitical factors on translation strategies, demonstrating how modern translation theory integrates both linguistic precision and communicative effectiveness. By reviewing historical and contemporary perspectives, this study provides insights into the ongoing transformation of translation as a scholarly discipline and practical profession.